One new species of the genus Acosmetides Chang, Wang & Shi, 2021 (Tettigoniidae: Meconematinae) from Chongqing, China - Wang, Yang; Duan, Yueting; Chang, Yanlin (Zootaxa, 2024)
This paper reports one new species of the genus Acosmetides from Chongqing, China, i.e. Acosmetides furcutusa sp. nov. Morphological photographs of the new species are provided.